2019
DOI: 10.1002/ange.201904658
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Indoles through Domino Reactions of 2‐Fluorotoluenes and Nitriles

Abstract: Indoles are essential heterocycles in medicinal chemistry,a nd therefore,n ovel and efficient approaches to their synthesis are in high demand. Among indoles,2 -aryl indoles have been described as privileged scaffolds.Advanced herein is astraightforward, practical, and transition-metal-free assembly of 2-aryl indoles.Simply combining readily available 2-fluorotoluenes,n itriles,L iN(SiMe 3 ) 2 ,a nd CsF enables the generation of adiverse arrayofindoles (38 examples,48-92 % yield). Ar ange of substituents can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 101 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Based on the above investigation and literature reports, [82][83][84][85][86][87][88][89][90] a possible mechanism is proposed in Fig. 5.…”
Section: Cycloaddition Reaction (3u)mentioning
confidence: 90%
See 2 more Smart Citations
“…Based on the above investigation and literature reports, [82][83][84][85][86][87][88][89][90] a possible mechanism is proposed in Fig. 5.…”
Section: Cycloaddition Reaction (3u)mentioning
confidence: 90%
“…The resulting alkenyl-metal species C undergoes protonation and 1,5-hydrogen shift process to deliver the desired 3a. Alternatively, the reaction could proceed by either protonation or silylation of intermediate B with HN(SiMe 3 ) 2 from the initial deprotonation equilibrium, generating imine D. 82 In the presence of Li/KN(SiMe 3 ) 2 , the imine D would undergo a reversible addition, silyl migration, and elimination pathway to release nitrogen-exchanged intermediate F, 91,92 followed by the further silyl transfer and cyclization to give nitrogen-exchanged intermediate G.…”
Section: Cycloaddition Reaction (3u)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hidetoshi Tokuyama et al [15] have reported cascade process for construction of N-linked indoles 108 (scheme 36) on 3aposition of pyrroloindoline 105. [56] In this process Bromopyrroloindoline 105 undergo silver catalysed one-pot amination with 2-ethynyl anilines 106 through 5-endo-dig cyclization in the presense of DTPB as an oxidant in dichloromethane solvent. The bromo group and alkyne moiety are activated by AgNTf 2 as α-Lewis acid and π-Lewis acid respectively.…”
Section: Silver-catalysed Synthesis Of Indolesmentioning
confidence: 99%
“…To our delight, the proposed tandem strategy could be successfully realized to afford C-N bond-forming (Bariwal and Van der Eycken, 2013) product 3a in 74% NMR yield (70% isolated yield; Table 1, entry 1). Notably, the excellent performance of the reaction required the simultaneous use of cobalt salt, additive TBAB, and base (Mao et al, 2019;Xue et al, 2015) (Table 1, entries 2-4), as the reaction proceeded with reduced efficiency in the absence of any of them. It is noteworthy that decreasing reaction temperature even to room temperature still gave the same good yield of the product 3a (Table 1, entry 5).…”
Section: Optimization Of Reaction Conditionsmentioning
confidence: 99%